2017
DOI: 10.1007/s11356-017-0699-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction with Salix viminalis in a moderately to strongly contaminated area

Abstract: We tested the suitability of Salix viminalis for phytoextraction with the analysis of selected elements in soil, root, and leaf, and by visual tree condition assessment in an area with varying levels of contamination. Bioconcentration factor (BCF) and translocation factor (TF) were used to assess the phytoextraction potential of willows. The middle part of the study area was strongly contaminated, while the northern and southern parts were moderately contaminated. We found increasing element concentrations tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…Hussain et al (2017) explained the four-degree scale where BF < 0.01 indicates no accumulation, 0.01-0.1 low accumulation (0.01-0.1), medium accumulation (0.1-1.0) and > 1.0 high bioaccumulation. Salix species have been widely-studied regarding their potential to translocate metals from roots to aerial parts (Tőzsér et al, 2017). Salix growing on the polluted soils have different metals accumulation capacity as well as high genetic variability in growth rates (Salam et al, 2016;Yang et al, 2014;Zhivotovsky et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Hussain et al (2017) explained the four-degree scale where BF < 0.01 indicates no accumulation, 0.01-0.1 low accumulation (0.01-0.1), medium accumulation (0.1-1.0) and > 1.0 high bioaccumulation. Salix species have been widely-studied regarding their potential to translocate metals from roots to aerial parts (Tőzsér et al, 2017). Salix growing on the polluted soils have different metals accumulation capacity as well as high genetic variability in growth rates (Salam et al, 2016;Yang et al, 2014;Zhivotovsky et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Soil degradation may also be due to fires, prolonged droughts, strong winds, invasive vegetation, municipal waste (may contain nonbiodegradable organics and heavy metal such as Pb, Cd or Zn), heavy metal mining, gold mining and industrial activities, especially chemical and/or petrochemical plants. At the level of 1991, it was estimated that about 240 Mha of land chemically degraded, representing 12% of total degraded soils [5,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that Salix viminalis absorbed the largest amount of heavy metals from soil, absorbing 84 % of Cd, 90% of Cu, 167% of Hg, 190% of Pb and 36% of Zn, and, following the accumulation of heavy metals, the cellulose content increased from 42.09 to 49.69%. Tőzsér et al [17] studied the possibility of using Salix viminalis for the phytoextraction of metals and other contaminants, such as Al, Ca, K, Mg, Ni, Sr and Zn, from soil. It was found that the average concentration of the chemical elements was the same in the roots and trunk but was much higher in the leaves of the energetic willow.…”
Section: Introductionmentioning
confidence: 99%
“…From the early 1970s, secondary treatment remained as the only function of the pond system, due to the establishment and continuous development of a modern wastewater treatment plant. The pond system had ceased to operate by the early 2000s (Tőzsér et al 2018). During the last decades of operation, the study area had been loaded with variable amounts of sewage sludge, contaminated with several macro-and microelements, such as toxic metals.…”
Section: Study Areamentioning
confidence: 99%
“…Soil samples were collected with a 50-mm Dutch soil auger from the three differently contaminated parts of the study area (northern -moderately contaminated part 1; middle -strongly contaminated part 2; southern -moderately contaminated part 3, after Tőzsér et al (2018); contamination levels were determined by Nagajyoti et al (2010) and Tóth et al (2016)) in late September 2015. We selected the soil sampling date to be in alignment with plant sampling near the end of the vegetation period.…”
Section: Soil Sampling and Analysismentioning
confidence: 99%